Penggunaan Bahasa Asing di Swiss-Belhotel Makassar - Ahmad Ab.; Kalis Nir Sambilaka; Sudarmi Sudarmi (Journal of Hospitality Accommodation Management (JHAM), 2023)
This study aims to investigate the proficiency of front office employees in speaking foreign languages at Swiss-Belhotel Makassar and the challenges they face in mastering foreign languages. The research utilized a qualitative approach, conducting interviews with front office department supervisors who assessed the employees' language proficiency. The findings revealed that the use of foreign languages, particularly English, is crucial in interacting with international guests at Swiss-Belhotel Makassar, especially in areas such as reservations, registration, and services for the room.